Effect of Mechanical Axis on Strain Distribution after Total Knee Replacement - Aroonjarattham, Panya; Aroonjarattham, Kitti; Suvanjumrat, Chakrit (Agriculture and Natural Resources, 2014)
A total knee replacement is one of the most successful orthopedic procedures to enable the patient’s return to a normal, active lifestyle. The angle of the mechanical axis depends on the surgeon’s decision, which effects the strain distribution on the femoral bone and may lead to a fracture of the femur . This study evaluated the equivalent total strain on the femoral shaft under daily activities using various models of the lower extremity with a varus knee deformity and the lower extremity with a total knee prosthesis, which was inserted at five different angles—0°, 3° valgus, 5° valgus, 3° varus and 5° varus. The results showed that the insertion of a total knee replacement in the case of a bowleg helped to reduce the equivalent total strain on the bone. The position of the prosthesis with a 3° valgus angle produced less strain distribution on the femoral bone. From the results, the mechanical axis affected the risk of the bone fracture. Considering the plastic spacer, it was found that there was an increase in the von Mises stress in the medial side of the model leg with a knee prosthesis of 3° valgus.